Krytyka dziewiętnastowiecznego rozumu. Źródła i konteksty Pałuby Karola Irzykowskiego - Jauksz, Marcin (My University, 2010)
The author interprets one of the crucial novels of the Young Poland in the context of prominent nineteenth and twentieth century literary works in order to show its prominent aspect – the fact of its being a document of its author experience. Due to the setting of The Hag alongside the literary pieces of Henryk Sienkiewicz, Stendhal, Stanisław Brzozowski, Edgar Alan Poe, Kazimierz Przerwa-Tetmajer and Wacław Berent and the work of philosophers like Immanuel Kant, Arthur Schopenhauer, Friedrich Nietzsche and Ernst Mach it is possible to show the point of Karol Irzykowski’s experiment and its very important connection between his work, which has been thought of as polemical towards the Young Poland, and its literary times, to which it owes, as it is proven, more than a lot. The new interpretation of the self-referential parts of The Hag establishes a significant relation towards its author biography as the important origin of Irzykowski’s “poetry” and enables to define a new concept of author’s subject within a work of art which the writer wanted to create.

Zadaniem pracy jest interpretacja jednej z kluczowych powieści młodopolskich w kontekście dziewiętnasto- i dwudziestowiecznych dzieł literackich i filozoficznych jako istotnego dokumentu doświadczeń twórcy. Dzięki lekturze Pałuby obok utworów Henryka Sienkiewicza, Stendhala, Stanisława Brzozowskiego, Edgara Alana Poe, Kazimierza Przerwy-Tetmajera, Wacława Berenta oraz na tle myśli filozoficznej Immanuela Kanta, Arthura Schopenhauera, Fryderyka Nietzschego oraz Ernsta Macha ujawnia się istota ekspresywistycznego eksperymentu Karola Irzykowskiego oraz niezwykle istotne związki między jego dziełem, które uznawane za jawnie polemiczne względem Młodej Polski, a epoką, z którą okazuje się mieć bardzo wiele wspólnego. Dzięki nowemu odczytaniu autotematycznych fragmentów Pałuby, ujawnia się znaczenie autobiograficznych danych jako ważnego źródła „poezji” Irzykowskiego i autorska koncepcja podmiotu autorskiego, jaką dla dzieł literackich pragnął wypracować Irzykowski.
Critique of Nineteenth-Century Reason. Origins and Contexts of Karol Irzykowski’s “The Hag”
Wydział Filologii Polskiej i Klasycznej: Instytut Filologii Polskiej
Keywords: Młoda Polska; Young Poland; intertekstualność; intertextuality; ekspresja; expression; autotematyzm; self-reflection; doświadczenie; experience